Superlubrication properties of ultra-nanocrystalline diamond film sliding against a zirconia ball. Issue 122 (24th November 2015) - Rani, Revati; Kumar, N.; Kozakov, A. T.; Googlev, K. A.; Sankaran, K. J.; Das, Pankaj Kr.; Dash, S.; Tyagi, A. K.; Lin, I-Nan
Abstract : The friction and wear behavior of ultra-nanocrystalline diamond (UNCD) films are sensitive to the phase composition, mainly graphite and amorphous carbon (a-C), occupying the grain boundaries of sp 3 hybridized diamond nanocrystals. Abstract : The friction and wear behavior of ultra-nanocrystalline diamond (UNCD) films are sensitive to the phase composition, mainly graphite and amorphous carbon (a-C), occupying the grain boundaries of sp 3 hybridized diamond nanocrystals. A large volume fraction of the grain boundary phase was observed when the diamond was grown in a CH4 (6%)/N2 plasma medium, and this film exhibited reduced hardness. However, the grain boundary phase was suppressed and a harder sp 3 hybridized volume fraction of nanocrystals dominated in CH4 (1%)/Ar plasma grown film. Two distinctly different friction and wear behaviors were observed in these films while sliding against a ZrO2 ceramic ball. High wear and mechanical deformation of the ZrO2 ball were seen while sliding against the hard film and wear loss from the film was rather marginal. In contrast, in the case of a soft film, the wear loss from the film was found to be significantly higher with the ball being marginally deformed. Such behavior is explained by hard and soft contact combinations composed of the ball and film interface. Wear occurs easily when the lamellar graphite structure dominates in the film, which becomes depleted by a shear force. Very high friction coefficients of up to 0.6 and high wear loss at the beginning of the sliding cycles were observed in these films. This is explained by a residual layer of graphite and a-C contaminated by oxygen functional groups. Interestingly, the friction coefficient reduced to the super-low value of 0.008 with a lack of wear once the contaminated layer was delaminated and exhibited sliding with a saturated sp 3 rich phase. This was detected in X-ray photoelectron spectra obtained from the wear tracks formed at different sliding distances. A mechanochemical model is proposed to reveal the run-in period friction/wear behavior which largely depends on the chemical interaction of the oxidized interfaces.